THE EXPOLARIZATION OF NARCISSISTIC BEHAVIOR IN MODERN MUSLIM WOMEN ON TIKTOK SOCIAL MEDIA: Between Identity and Existence - Dama Nazila, Salwa; Sugiarto, Fitrah; Orwela, Citra (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
The rapid advancement of technology has made social media more accessible, facilitating digital interactions that shape mindsets and perspectives. However, social media development has also had negative societal impacts. This study employs a qualitative method with a library research approach. Data is obtained through the analysis of Qur'anic texts, interpretations, scholarly opinions, and other literature, focusing on narcissistic attitudes (tabarruj) and legal perspectives, as well as offering solutions to narcissistic behavior on social media platforms. The study aims to analyze how Muslim women present themselves on TikTok, identify manifestations of digital narcissism, examine the social, psychological, and cultural factors influencing this behavior, provide an Islamic perspective on tabarruj in the context of social media, and suggest solutions for more mindful digital engagement. Using a qualitative approach, this research investigates Qur’anic interpretations, scholarly discussions, and various literature related to digital narcissism. The findings indicate that digital narcissism among Muslim women on TikTok is reflected in behaviors such as excessive self-presentation, seeking validation through likes, comments, and followers, and the influence of social media aesthetics in shaping identity. Factors contributing to this behavior include the impact of popular culture, social pressures, and psychological dependence on external validation, which can ultimately diminish self-confidence. Therefore, raising awareness through education is essential to preserving Islamic identity in the digital era. It is hoped that social media users, particularly Muslim women, will be more selective in creating and consuming content while prioritizing moral values and simplicity in online interactions.